Effects of sacubitril/valsartan versus valsartan on renal function in patients with and without diabetes and heart failure with preserved ejection fraction: insights from PARAGON‐HF. (15th February 2022) - Peikert, Alexander; Vaduganathan, Muthiah; Mc Causland, Finnian; Claggett, Brian L.; Chatur, Safia; Packer, Milton; Pfeffer, Marc A.; Zannad, Faiez; Lefkowitz, Martin P.; Pieske, Burkert; Düngen, Hans‐Dirk; McMurray, John J.V.; et al.
Abstract : Aims: Diabetes is associated with a faster rate of renal function decline in patients with heart failure (HF). Sacubitril/valsartan attenuates the deterioration of renal function to a greater extent in patients with diabetes and HF with reduced ejection fraction compared with renin–angiotensin system inhibitors alone. We assessed whether the same may be true in HF with preserved ejection fraction (HFpEF). Methods and results: In the PARAGON‐HF trial in patients with HF and left ventricular ejection fraction of ≥45% ( n = 4796), we characterized the effects of sacubitril/valsartan on changes in estimated glomerular filtration rate (eGFR) over a period of 192 weeks, and on the pre‐specified renal composite outcome (eGFR reduction of ≥50%, end‐stage renal disease, or death attributable to renal causes) in patients with ( n = 2388) and without diabetes ( n = 2408). The decline in eGFR was greater in patients with diabetes than in those without (−2.6 vs. −1.7 ml/min/1.73 m 2 per year, p < 0.001), regardless of treatment assignment. Sacubitril/valsartan attenuated decline in eGFR similarly in patients with (−2.2 vs. −2.9 ml/min/1.73 m 2 per year, p = 0.001) and without diabetes (−1.5 vs. −2.0 ml/min/1.73 m 2 per year, p = 0.006) ( p interaction for difference in eGFR slopes = 0.40). Compared with valsartan, sacubitril/valsartan reduced the renal composite outcome similarly in patients without diabetes (hazard ratio [HR] 0.42, 95% confidence interval [CI] 0.19–0.91) and those with diabetes (HR 0.54, 95% CI 0.33–0.89; p interaction = 0.59), as well as across a range of baseline glycated haemoglobin ( p interaction = 0.71). Conclusion: Sacubitril/valsartan, compared with valsartan, attenuates the decline of eGFR and reduces clinically relevant kidney events similarly among patients with HFpEF with and without diabetes. Abstract : Treatment effect of sacubitril/valsartan (Sac/Val) on changes in estimated glomerular filtration rate (eGFR) over time and the renal composite outcome in patients with and without diabetes. Adjusted means for eGFR over a period of 192 weeks were obtained from repeated‐measures mixed‐effect models. Error bars indicate 95% confidence intervals. eGFR was calculated according to the Chronic Kidney Disease Epidemiology Collaboration equation. Estimates of the probability of a first occurrence of the renal composite outcome (eGFR reduction of ≥50% relative to baseline, development of end‐stage renal disease, or death attributable to renal causes) were obtained from Kaplan–Meier failure analyses. HR, hazard ratio.